High-energy density nanofiber-based solid-state supercapacitors. Issue 1 (30th November 2015) - Lawrence, Daniel W.; Tran, Chau; Mallajoysula, Arun T.; Doorn, Stephen K.; Mohite, Aditya; Gupta, Gautam; Kalra, Vibha
Abstract : We have developed binder-free solid-state electric double layer supercapacitors using freestanding porous carbon nanofiber electrodes fabricated using electrospinning and silica-based ionic liquid gel electrolytes. Abstract : We have developed binder-free solid-state electric double layer supercapacitors using freestanding porous carbon nanofiber electrodes fabricated using electrospinning and silica-based ionic liquid gel electrolytes. To ensure close electrode/electrolyte contact and efficient transport of ions for high power operation, we fabricated our electrodes by uniformly filling freestanding samples of porous carbon nanofiber mats with a blend of silica sol–gel precursor and ionic liquid electrolyte, which were then appropriately dried/gelled to form all-solid supercapacitors. Two different carbon nanofiber samples have been investigated with high specific surface areas of 1218 m 2 g −1 and 2282 m 2 g −1 . The resulting solid-state supercapacitor can operate in a large voltage window of 3.5 V. We achieved specific capacitance ( C sp ) and specific energy ( E cell, based on the mass of the two electrodes) of up to 144 F g −1 and 61 W h kg −1 respectively, rivaling that of lead-acid batteries, with a high active material (carbon only) loading of 3–5 mg cm −2 .